2018
DOI: 10.1038/s41431-018-0173-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional characterization of the CDH1 germline variant c.1679C>G in three unrelated families with hereditary diffuse gastric cancer

Abstract: Germline changes in the CDH1 tumor suppressor gene predispose to diffuse gastric cancer and lobular breast cancer. In carriers of deleterious germline CDH1 variants, prophylactic gastrectomy is recommended. In case of germline missense variants, it is mandatory to assess the functional impact on E-cadherin, the protein encoded by CDH1, and to predict their clinical significance. Herein, we have identified a recurrent germline missense variant, c.1679C>G, segregating with gastric cancer in three unrelated Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…For the family study articles, we collected data on country (or ethnicity), mutation type and classification, age of proband, total number of screened subjects harbouring CDH1 mutations, number of carriers affected by gastric cancer, and number of carriers affected by other cancer types ( Table S2 ) [ 18 , 37 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Mean age of CDH1 mutation carriers affected by gastric cancer and mean age of carriers affected by other cancer types was also determined.…”
Section: Methodsmentioning
confidence: 99%
“…For the family study articles, we collected data on country (or ethnicity), mutation type and classification, age of proband, total number of screened subjects harbouring CDH1 mutations, number of carriers affected by gastric cancer, and number of carriers affected by other cancer types ( Table S2 ) [ 18 , 37 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Mean age of CDH1 mutation carriers affected by gastric cancer and mean age of carriers affected by other cancer types was also determined.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining and its detailed quantitative analysis is then used to address whether the variant induces abnormal patterns of E-cadherin localization [136]. Occasionally, a band mobility shift can also be observed, suggesting aberrant glycosylation of the protein [138,139]. Contrary to wild-type E-cadherin, which is normally present at the plasma membrane, deleterious variants can be diffusely distributed throughout the cell or abnormally accumulated in cytoplasmic regions/organelles [135,136,140].…”
Section: Cdh1 Missense Variants: Challenging Routine Laboratory Testsmentioning
confidence: 99%
“…Here we present an HDGC family with a missense CDH1 substitution variant, c.1679C>G (p.T560R). The p.T560R variant had been reported three times in patients with HDGC[ 11 - 13 ]. Yelskaya et al [ 12 ] reported that the p.T560R mutation created a novel 5¢ splice donor site that led to truncation of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Yelskaya et al [ 12 ] reported that the p.T560R mutation created a novel 5¢ splice donor site that led to truncation of E-cadherin. Furthermore, Pena-Couso et al [ 13 ] performed functional analyses, which revealed that the p.T560R mutation causes an abnormal pattern of E-cadherin expression in the cytoplasm, disrupts cell-cell adhesion and promotes cellular invasion. Consistent with these reports, loss of E-cadherin expression at SRCC foci was observed in Case 3.…”
Section: Discussionmentioning
confidence: 99%